2018
DOI: 10.1007/s00262-018-2197-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with cancer peptides in combination with intravesical bacillus Calmette–Guerin for patients with non-muscle invasive bladder cancer

Abstract: Cancer peptide vaccines in combination with intravesical BCG therapy demonstrated good immunogenicity and safety, and may provide benefit for preventing recurrence of NMIBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 29 publications
2
20
1
Order By: Relevance
“…DEPDC1 is highly expressed in various kinds of cancers, like bladder cancer, hepatocellular carcinoma, lung cancer, and nasopharyngeal carcinoma (18, 2427). Its abnormal expression drives the progression of carcinogenesis and the malignant behavior of cancer cells (12, 28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DEPDC1 is highly expressed in various kinds of cancers, like bladder cancer, hepatocellular carcinoma, lung cancer, and nasopharyngeal carcinoma (18, 2427). Its abnormal expression drives the progression of carcinogenesis and the malignant behavior of cancer cells (12, 28).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, DEPDC1 promoting cancer development was gradually discovered and had been widely considered as a putative oncogene. The role of DEPDC1 in cancers was mainly found in bladder cancer (8, 10, 24, 29, 30). It was reported that DEPDC1 was significantly increased in bladder carcinoma and necessary for the proliferation of cancer cells (8).…”
Section: Discussionmentioning
confidence: 99%
“…In view of our results, further investigation is warranted to elucidate the complete immune response (other immune subsets of cells or local and systemic immune biomarkers) induced by M. brumae compared to BCG to completely understand the role of mycobacteria in modulating the tumor microenvironment. Different strategies for superficial bladder treatment are currently being proposed: diverse bacteria 30 – 32 , modified virus 33 , 34 , chemotherapeutic agents 35 , molecules that target specific immune receptors 36 , peptide vaccines 37 , plant derived compounds 38 , etc. Mycobacteria can have a role to synergy to these treatments, as has been already demonstrated 35 , 37 , 38 , enabling to reduce the toxicity and resistance to a single treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Different strategies for superficial bladder treatment are currently being proposed: diverse bacteria 30 – 32 , modified virus 33 , 34 , chemotherapeutic agents 35 , molecules that target specific immune receptors 36 , peptide vaccines 37 , plant derived compounds 38 , etc. Mycobacteria can have a role to synergy to these treatments, as has been already demonstrated 35 , 37 , 38 , enabling to reduce the toxicity and resistance to a single treatment. Further understanding of the immune reaction associated with mycobacteria treatment could be critical for identifying the benefits of new immunotherapeutic possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a preclinical study, researchers observed that, in a syngeneic mouse model of oral cancer comprised of mouse tonsil-derived epithelial cells stably expressing HPV-16 E6 and E7 genes along with H-ras oncogene (mEER), intranasal HPV E6/E7 peptide vaccination or single checkpoint antibodies failed to elicit responses in most mice; however, 4-1BB agonist antibody along with either CD40 agonist antibody or CTLA-4 blockade eliminated the majority of established mEER tumors, and even produced a curative efficacy and a high safety profile against orally implanted mEER tumors [40]. For another example, in a phase II clinical trial, researchers performed immunotherapy with two peptide cancer vaccines in combination with intravesical bacillus Calmette-Guerin (BCG) for patients with non-muscle invasive bladder cancer (NMIBC) and demonstrated that this combinatory immunotherapy had good immunogenicity and safety and resulted in a 2 year RFS rate 74.0% in all patients, suggesting the cancer vaccines with a combinatory mode may provide benefit to patients for preventing recurrence of NMIBC [41].…”
Section: Np Entrapping Various Ags For Delivering Cancer Vaccinesmentioning
confidence: 99%